(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims to determine the principles of total quality management (commitment of senior management, product planning, customer satisfaction, process improvement) and its role in promoting employee loyalty through a sample survey of the opinions of managers in public redemption Company. Which amounted to (45) individuals adoption of the questionnaire as a tool head in collecting data and information and their responses were analyzed using several statistical methods, which included (arithmetic mean, standard deviation, correlation coefficient, and the coefficient of simple regression) depending on the program (spss). The research found a group of the most important conclusions from the presence of correlation and the impact is significant morale between the principles of total quality management and enhancing employee loyalty in the company surveyed.